Distinct Roles for MyD88 and Toll-Like Receptor 2 during Leishmania braziliensis Infection in Mice - Vargas-Inchaustegui, Diego A. (American Society for Microbiology (ASM), 2009)
We have previously reported that Leishmania braziliensis infection can activate murine dendritic cells (DCs) and upregulate signaling pathways that are essential for the initiation of innate immunity. However, it remains unclear whether Toll-like receptors (TLRs) are involved in L. braziliensis-mediated DC activation. To address this issue, we generated bone marrow-derived DCs from MyD88(−/−) and TLR2(−/−) mice and examined their responsiveness to parasite infection. While wild-type DCs were efficiently activated to produce cytokines and prime naïve CD4(+) T cells, L. braziliensis-infected MyD88(−/−) DCs exhibited less activation and decreased production of interleukin-12 (IL-12) p40. Furthermore, MyD88(−/−) mice were more susceptible to infection in that they developed larger and prolonged lesions compared to those in control mice. In sharp contrast, the lack of TLR2 resulted in an enhanced DC activation and increased IL-12 p40 production after infection. As such, L. braziliensis-infected TLR2(−/−) DCs were more competent in priming naïve CD4(+) T cells in vitro than were their controls, findings which correlated with an increased gamma interferon production in vivo and enhanced resistance to infection. Our results suggest that while MyD88 is indispensable for the generation of protective immunity to L. braziliensis, TLR2 seems to have a regulatory role during infection.